2012
DOI: 10.1177/1468017311435445
|View full text |Cite
|
Sign up to set email alerts
|

Managing intimate partner violence at the social services department of a Greek university hospital

Abstract: Although abused patients are thought to access the health system at a range of potential entry points, social services are usually the only referral option within the various hospital sectors. In Greece, little is known about the prevalence of intimate partner violence (IPV) and the quality of care provided to cases of abuse at the social services. The current study explored the department's response to IPV cases in a Greek university hospital. Two different research methods were employed: qualitative and docu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 45 publications
0
4
1
Order By: Relevance
“…Another noteworthy finding of the current study is that high numbers of participants in both professional groups reported sufficient to high confidence in their skills to assess and manage IPV. The current finding is not consistent with previous findings in Greek health care professionals (Papadakaki et al, 2012b;Zidianakis et al, 2009) and findings from other countries indicating low confidence of health care providers in addressing the problem Sugg & Inue, 1992). The low perceived IPV educational attainment reported by the participants in the current study does not either justify this finding.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Another noteworthy finding of the current study is that high numbers of participants in both professional groups reported sufficient to high confidence in their skills to assess and manage IPV. The current finding is not consistent with previous findings in Greek health care professionals (Papadakaki et al, 2012b;Zidianakis et al, 2009) and findings from other countries indicating low confidence of health care providers in addressing the problem Sugg & Inue, 1992). The low perceived IPV educational attainment reported by the participants in the current study does not either justify this finding.…”
Section: Discussioncontrasting
confidence: 99%
“…This knowledge gap of home care practitioners seems quite alarming and undrlines the need for more comprehensive IPV education. Poor IPV education has been demonstrated in previous studies of Greek social workers, nurses and general practitioners employed in other health care settings (Androulaki et al, 2008;Chatzifotiou et al, 2012;Papadakaki et al, 2012b;Zidianakis et al, 2009). This finding is not surprising as undergraduate social work curricula in Greece, in all four higher education social work institutes make limited if any reference to violence against women (Papadakaki et al, 2012b).…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…Financial constraint is one of the major obstacles for many women who experience IPV when it comes to making a decision about whether they are staying in or leaving a violent relationship (Carlson, McNutt, Choi, & Rose, 2002; Tam, 2004; WHO, 2002). Women with limited financial resources, for instance, have to consider whether they should get medical treatment and/or injury assessment at hospitals or save the money for basic needs such as food, housing, and clothing for their children (Papadakaki, Kastrinaki, Drakaki, & Chliaoutakis, 2012; Pyles, 2006; Tam, Kwok, Wu, Law, & Chan, 2009; WHO, 2005b).…”
Section: Local Contextmentioning
confidence: 99%